Flexible perovskite solar cell and preparation method thereof

By using the method of combining ALD and spin coating in flexible perovskite solar cells to prepare a dense electron transport layer, the problem of insufficient dense and high-temperature treatment in the prior art is solved, and efficient perovskite layer crystallization and the improvement of photoelectric conversion efficiency of solar cells is achieved.

CN119836186AActive Publication Date: 2025-04-15HUAZHONG UNIV OF SCI & TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510021296.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

In the preparation process of existing flexible perovskite solar cells, the electron transport layer is not dense enough, the solution causes corrosion to the substrate, resulting in a drop in the filling factor and open circuit voltage of the battery, and requires high temperature treatment, which violates the characteristics of the flexible substrate.

Method used

An electron transport layer was prepared by combining atomic layer deposition (ALD) and spin coating. By depositing a SnO2 layer on the substrate and spin-coating SnO2 dispersion doped with glycine hydrochloride, it was subjected to low-temperature annealing to form a dense and uniform electron transport layer.

Benefits of technology

It realizes the preparation of electron transport layers with dense structure and flat surfaces at low temperatures, avoids substrate corrosion, improves the crystallization effect of the perovskite layer, and improves the photoelectric conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836186A_ABST
    Figure CN119836186A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible perovskite solar cell and a preparation method thereof. The preparation of the electron transport layer of the flexible perovskite solar cell comprises the steps of depositing a SnO2 layer on a substrate through an atomic layer deposition method, spin-coating a SnO2 dispersion liquid doped with glycine hydrochloride on the obtained SnO2 deposition layer to form a SnO2 spin-coating layer, obtaining a double-SnO2-layer structure containing the SnO2 deposition layer and the SnO2 spin-coating layer, and annealing the double-SnO2-layer structure at 80-100 DEG C to obtain the electron transport layer of the flexible perovskite solar cell. The flexible perovskite solar cell electron transport layer is compact and uniform in structure, can be prepared at a low temperature, is corrosion-resistant, and can promote the crystallization effect of a perovskite layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to the technical field of flexible perovskite solar cells. Background Art

[0002] Perovskite solar cells (PSCs) are a new type of solar cell that has received the most attention in recent years and has the fastest increasing photoelectric conversion efficiency (PCE). The photoelectric conversion efficiency (PCE) of a single-junction cell has climbed to 26.9%. At the same time, PSCs also have the advantages of being cheap and flexible, showing great development potential in the field of flexible photovoltaics.

[0003] However, there are still many problems in the preparation process of flexible perovskite solar cells in the existing technology. The key problem is that the electron transport layer prepared by methods such as spin coating and chemical bath deposition is not dense enough and the solution will corrode the substrate, resulting in a significant decrease in the fill factor and open circuit voltage of the battery. In addition, the above methods require high-temperature post-treatment, which is contrary to the high-temperature resistant characteristics of the flexible substrate, which significantly limits the further application of flexible PSCs. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a new flexible perovskite solar cell and a preparation method thereof. The flexible perovskite solar cell has a corrosion-resistant electron transport layer with a compact and uniform structure and a flat surface, can be prepared at low temperature, and can promote the crystallization effect of the perovskite layer.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a flexible perovskite solar cell, comprising:

[0007] Obtaining a substrate for depositing an electron transport layer for a flexible perovskite solar cell;

[0008] preparing a flexible perovskite solar cell electron transport layer on the substrate;

[0009] Preparing a perovskite layer on the flexible perovskite solar cell electron transport layer;

[0010] preparing an n-butylammonium iodide passivation layer on the perovskite layer;

[0011] preparing a hole transport layer on the n-butylammonium iodide passivation layer;

[0012] preparing a metal electrode on the hole transport layer;

[0013] Wherein, the preparation of the electron transport layer of the flexible perovskite solar cell comprises:

[0014] (1) Deposition of SnO on substrate by atomic layer deposition 2 layer, to obtain SnO 2 Sedimentary layers;

[0015] (2) To the SnO 2 Spin-coat SnO doped with glycine hydrochloride on the deposited layer 2 dispersion, forming SnO 2 Spin coating, the obtained SnO 2 Deposition layer and SnO 2 Spin-coated double SnO 2 The layer structure is subjected to a first annealing treatment in air at a temperature of 80-100° C. to obtain the flexible perovskite solar cell electron transport layer.

[0016] Wherein, the SnO doped with glycine hydrochloride 2 The dispersion is obtained by:

[0017] Add SnO to the deionized water solution of glycine hydrochloride 2 After mixing evenly, the SnO doped with glycine hydrochloride is obtained. 2 Dispersion.

[0018] The electron transport layer of the present invention contains SnO deposited by ALD method. 2 layer, which has a dense structure and can protect the flexible substrate from SnO 2 Solution corrosion.

[0019] According to some preferred embodiments of the present invention, the SnO 2 The thickness of the deposited layer is 18-50 nm, more preferably 30 nm.

[0020] According to some preferred embodiments of the present invention, the SnO 2 The thickness of the spin-coated layer is 20-30 nm, more preferably, 25-35 nm.

[0021] According to some preferred embodiments of the present invention, the SnO 2 SnO in aqueous dispersion 2 The concentration is 10-20wt%.

[0022] According to some preferred embodiments of the present invention, the deionized water solution of glycine hydrochloride and the SnO 2 The volume ratio of the aqueous dispersion is 4-6:1.

[0023] According to some preferred embodiments of the present invention, the atomic layer deposition method comprises: at a pressure of 2×10 -4 Pa-4×10-4 Pa, a carrier gas flow rate of 20-40 sccm, and a temperature of 80-100°C, the following were performed: (a) ultrapure water pulse injection for 0.01-0.02 s, followed by a waiting time of 3-5 s; (b) tetrakis(dimethylamino)tin (TDMASn) source pulse injection for 0.05-0.15 s, followed by a waiting time of 3-5 s; the process of (a)-(b) was then repeated 200-300 times, followed by a natural cooling to 55-65°C.

[0024] According to some preferred embodiments of the present invention, the spin coating comprises: applying the SnO doped with glycine hydrochloride 2 The dispersion is spin-coated on the SnO 2 On the sedimentary layer.

[0025] According to some preferred embodiments of the present invention, in the atomic layer deposition method, the water-oxygen ratio of the deposition is 0.02-0.03.

[0026] According to some preferred embodiments of the present invention, in the atomic layer deposition method, the process (a)-(b) is repeated 250 times.

[0027] According to some preferred embodiments of the present invention, the substrate is selected from polyethylene terephthalate coated with indium tin oxide conductive material (PEN / ITO).

[0028] According to some preferred embodiments of the present invention, the preparation method comprises:

[0029] (1) pretreating a polyethylene terephthalate-coated indium tin oxide conductive material substrate by ultraviolet light to obtain a pretreated substrate;

[0030] (2) obtaining the flexible perovskite solar electron transport layer on the pretreated substrate to obtain a substrate containing the electron transport layer;

[0031] (3) Formamidine hydroiodide (FAI), methylammonium chloride (MACl), lead iodide (PbI 2 ) is dissolved in a mixed solution of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) to form a perovskite precursor solution, which is spin-coated on the substrate containing the electron transport layer, chlorobenzene is added dropwise during the spin coating process, and a second annealing treatment is performed after the spin coating is completed to obtain a substrate containing the perovskite layer;

[0032] (4) dissolving a passivating agent, n-butylammonium iodide (BAI), in isopropanol to obtain a passivating precursor solution, which is spin-coated on the substrate of the perovskite layer, and performing a third annealing treatment after the spin coating is completed to obtain a substrate containing a passivation layer;

[0033] (5) dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) in chlorobenzene, adding 4-tert-butylpyridine (tBP) and acetonitrile solution of lithium bis(trifluoromethane)sulfonyl imide (Li-TFSI) to obtain a hole precursor solution, spin-coating the solution on the substrate containing the passivation layer, and drying the solution after spin coating to obtain a substrate containing a hole transport layer;

[0034] (6) Depositing silver as a metal electrode on the substrate containing the hole transport layer by thermal evaporation to obtain a flexible perovskite solar cell.

[0035] According to some preferred embodiments of the present invention, the pretreatment further comprises cutting the polyethylene terephthalate coated indium tin oxide conductive material into a size of 1.5 cm×1.5 cm.

[0036] According to some preferred embodiments of the present invention, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 1:4, the concentration of methylamine chloride is 0.1-1.0 mol / ml, the concentration of formamidine hydroiodide is 1.0-2.0 mol / ml, and the concentration of lead iodide is 1.0-2.0 mol / ml.

[0037] According to some preferred embodiments of the present invention, in the passivation precursor solution, the concentration of n-butylammonium iodide is 0.5-5 mg / mL, more preferably 2 mg / mL.

[0038] According to some preferred embodiments of the present invention, the deposition rate of the deposited silver is The thickness is 50-200 nm, more preferably, 100 nm.

[0039] According to some preferred embodiments of the present invention, the temperature of the second annealing treatment is 80-100° C., and the time is 10-40 min.

[0040] According to some preferred embodiments of the present invention, the temperature of the third annealing treatment is 70-90° C., and the time is 1-10 min.

[0041] According to the above preferred embodiments, the temperature of the entire preparation process of the flexible perovskite solar cell of the present invention can be controlled within 100° C., thereby avoiding bending of the flexible substrate at high temperatures.

[0042] According to some preferred embodiments of the present invention, the spin coating rotation speed in step (3) is 4400-4600 rpm, the speed increase is 1400-1600 rpm / s, the spin coating time is 20-30 s, and chlorobenzene is added dropwise at 15-19 s.

[0043] According to some preferred embodiments of the present invention, the spin coating rotation speed in step (4) is 4900-5100 rpm, the speed increase is 1900-2100 rpm / s, and the spin coating time is 25-35 s.

[0044] According to some preferred embodiments of the present invention, the spin coating rotation speed in step (5) is 3900-4100 rpm, the acceleration speed is 900-1100 rpm / s, and the spin coating time is 25-35 s.

[0045] According to some preferred embodiments of the present invention, the thickness of the deposited silver is 100 nm, and the deposition rate in the range of 0-5 nm is The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate for 50-100nm is

[0046] According to some specific embodiments of the present invention, the flexible perovskite solar cell obtained by the present invention is 2 Under the irradiation of simulated sunlight, an open circuit photovoltage of 1.14V and a current of 24.75mA / cm 2 The short-circuit photocurrent and photoelectric conversion efficiency of 23.51% were achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a schematic diagram of the structure of the flexible perovskite solar cell obtained in Example 1.

[0048] Figure 2 ALD SnO obtained in Example 1 2 Substrate and SnO of Comparative Examples 1-3 2 Atomic force microscopy comparison of the substrate.

[0049] Figure 3 ALD SnO obtained in Example 1 2 Substrate and SnO of Comparative Examples 1-3 2 SEM comparison of substrates.

[0050] Figure 4 ALD SnO obtained in Example 1 2 Substrate and SnO of Comparative Examples 1-3 2 Comparison of atomic force microscopy images of substrates after spin coating of perovskite layer.

[0051] Figure 5 This is a comparison diagram of X-ray diffraction of the perovskite solar cells obtained in Example 1 and Comparative Examples 1 and 3.

[0052] Figure 6 It is a comparative box plot of the power conversion efficiency (PCE), current density (Jsc), opening voltage (Voc) and fill factor (FF) of the perovskite solar cells obtained in Example 1 and Comparative Examples 1-3.

[0053] Figure 7 This is a graph showing the test results of the power conversion efficiency (PCE), current density (Jsc), opening voltage (Voc) and fill factor (FF) of the perovskite solar cell obtained in Example 1. DETAILED DESCRIPTION

[0054] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.

[0055] Example 1

[0056] Flexible perovskite solar cells were prepared by the following steps:

[0057] (1) Pretreatment of the substrate: Cut the PEN / ITO substrate into 1.5×1.5 cm size, remove the surface protective film, and then use a UV ozone cleaning machine to clean for 30 min to obtain a pretreated substrate;

[0058] (2) preparing an electron transport layer, including:

[0059] Preparation of SnO by ALD 2 Layer: After the sample chamber is inflated until the pressure reading reaches 760 torr, the chamber cover is opened and the pre-treated substrate is placed. The carrier gas flow rate is set to 30 sccm (1 sccm = 1 mL / min), the chamber temperature is 100 ° C, and after the temperature is stable for 120 s, ultrapure water pulse is sprayed for 0.015 s, and then wait for 4 s and then use TDMASn source pulse to spray for 0.1 s, wait for 4 s, and then cycle the process of ultrapure water pulse to TDMASn source pulse 250 times to complete the deposition. After the deposition is completed, wait for the temperature to drop back to 60 ° C to inflate and sample to obtain corrosion-resistant SnO 2 The substrate of the film;

[0060] Prepare a 4 mg / mL deionized water solution of glycine hydrochloride, wherein the purity of glycine hydrochloride is 99.8%. Take 212 μL of the obtained glycine hydrochloride solution and mix it evenly with 788 μL of deionized water, then slowly add 200 μL of SnO 2The 15% aqueous dispersion was stirred evenly to obtain a dispersion, and the dispersion was spin-coated on a surface containing anti-corrosion SnO at a rotation speed of 5000 rpm and a speed of 2000 rpm / s. 2 On the substrate of the film, a double-layer SnO 2 The substrate was placed on a constant temperature heating table and annealed in air for 60 minutes at a temperature of 100°C to obtain a substrate containing an electron transport layer, i.e., ITO(PEN) / SnO 2 ;

[0061] (3) preparing a perovskite layer, comprising:

[0062] 1.4 mol FAI, 0.42 mol MACl and 1.53 mol PbI 2 Dissolve in 800 μL of DMF and 200 μL of DMSO to form a perovskite precursor solution; then the prepared ITO(PEN) / SnO 2 The substrate was cleaned with a plasma cleaner for 5 minutes, and after cleaning, it was transferred to a nitrogen glove box together with the solution. The stirred perovskite precursor solution was spin-coated on the surface of the substrate containing the electron transport layer after cleaning at a speed of 4500 rpm and a speed of 1500 rpm / s for 25 seconds. At the 17th second of spin coating, 150 μL of chlorobenzene was added as an anti-solvent. After spin coating, it was transferred to a constant temperature hot stage for annealing for 30 minutes at a temperature of 100 °C to obtain a substrate containing a perovskite layer, namely, ITO (PEN) / SnO 2 / FAPB 3 ;

[0063] (4) Preparation of BAI passivation layer, including:

[0064] 2 mg BAI was dissolved in 1 ml isopropanol, stirred evenly, and the resulting solution was heated at 5000 rpm and 2000 rpm / s on an ITO (PEN) / SnO 2 / FAPB 3 The substrate was spin-coated for 30 seconds, and then annealed in a nitrogen environment for 5 minutes at a temperature of 80°C to obtain a substrate containing a BAI passivation layer, namely ITO (PEN).

[0065] / SnO 2 / FAPB 3 / BAI;

[0066] (5) Preparation of a hole transport layer, comprising:

[0067] 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of tBP and 17.5 μL of Li-TFSI (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile) were added to obtain a Spiro-OMeTAD precursor solution. The precursor solution was heated on ITO (PEN) / SnO 2 / FAPB 3 / BAI, spin coating at a rotation speed of 4000 rpm and a rising speed of 1000 rpm / s for 30 s, and after spin coating, transfer to a drying cabinet and store for 24 hours to obtain a substrate containing a hole transport layer;

[0068] (6) Preparation of metal electrodes, including:

[0069] A 100 nm silver layer was deposited as a metal electrode on a substrate containing a hole transport layer by thermal evaporation, wherein the deposition rate of 0 to 5 nm was The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate of 50-100 nm is A flexible perovskite solar cell is obtained, and its structure is as shown in the attached Figure 1 shown.

[0070] Comparative Example 1

[0071] The comparative perovskite solar cell was prepared by the following steps:

[0072] (1) Pretreatment of the substrate: Cut the PEN / ITO substrate into 1.5×1.5 cm size, remove the surface protective film, and then use a UV ozone cleaning machine to clean for 30 min to obtain a pretreated substrate;

[0073] (2) preparing an electron transport layer, including:

[0074] SnO 2 15% aqueous dispersion with H 2 O are mixed in a volume ratio of 1:5, stirred evenly, and then spin-coated on the pretreated substrate at a rotation speed of 5000 rpm and a speed increase of 2000 rpm / s. The spin-coated substrate is placed on a constant temperature heating table and annealed in air for 60 minutes at an annealing temperature of 100°C to obtain a substrate containing an electron transport layer;

[0075] (3) preparing a perovskite layer, comprising:

[0076] 1.4 mol FAI, 0.42 mol MACl and 1.53 mol PbI 2Dissolved in 800 μL of DMF and 200 μL of DMSO to form a perovskite precursor solution; then, the prepared substrate containing the electron transport layer was cleaned with a plasma cleaner for 5 minutes, and after cleaning, it was transferred to a nitrogen glove box together with the solution, and the stirred perovskite precursor solution was spin-coated on the surface of the cleaned substrate containing the electron transport layer at a speed of 4500 rpm and a speed of 1500 rpm / s for 25 seconds, and 150 μL of chlorobenzene was added as an anti-solvent at the 17th second of spin coating. After spin coating, it was transferred to a constant temperature hot stage for annealing for 30 minutes, and the annealing temperature was 100°C to obtain a substrate containing a perovskite layer;

[0077] (4) Preparation of BAI passivation layer, including:

[0078] 2 mg BAI was dissolved in 1 ml isopropanol, and after being stirred evenly, the obtained solution was spin-coated on the substrate containing the perovskite layer at a rotation speed of 5000 rpm and a speed increase of 2000 rpm / s for 30 seconds, and then annealed in a nitrogen environment for 5 minutes at an annealing temperature of 80°C to obtain a substrate containing a BAI passivation layer;

[0079] (5) Preparation of a hole transport layer, comprising:

[0080] 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of tBP and 17.5 μL of Li-TFSI (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile) were added to obtain a Spiro-OMeTAD precursor solution. The precursor solution was spin-coated on a substrate containing a BAI passivation layer at a rotation speed of 4000 rpm and a rise speed of 1000 rpm / s for 30 s. After the spin coating was completed, the substrate was transferred to a drying cabinet and stored for 24 hours to obtain a substrate containing a hole transport layer;

[0081] (6) Preparation of metal electrodes, including:

[0082] A 100 nm silver layer was deposited as a metal electrode on a substrate containing a hole transport layer by thermal evaporation, wherein the deposition rate of 0 to 5 nm was The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate of 50-100 nm is Comparative perovskite solar cells were obtained.

[0083] Comparative Example 2

[0084] The comparative perovskite solar cell was prepared by the following steps:

[0085] (1) Pretreatment of the substrate: Cut the PEN / ITO substrate into 1.5×1.5 cm size, remove the surface protective film, and then use a UV ozone cleaning machine to clean for 30 min to obtain a pretreated substrate;

[0086] (2) preparing an electron transport layer, including:

[0087] Preparation of SnO by ALD 2 Layer: After the sample chamber is inflated until the pressure reading reaches 760 torr, the chamber cover is opened and the pre-treated substrate is placed. The carrier gas flow rate is set to 30 sccm (1 sccm = 1 mL / min), the chamber temperature is 100 ° C, and after the temperature stabilizes for 120 seconds, ultrapure water pulse is sprayed for 0.015 seconds, and then wait for 4 seconds and then use TDMASn source pulse to spray for 0.1 seconds, wait for 4 seconds, and then cycle the process of ultrapure water pulse to TDMASn source pulse 150 times to complete the deposition. After the deposition is completed, wait for the temperature to drop back to 60 ° C to inflate and sample, and obtain 18nm corrosion-resistant SnO 2 The substrate of the film;

[0088] SnO 2 15% aqueous dispersion with H 2 O in a volume ratio of 1:5 and stirred evenly to obtain a dispersion, which was then spin-coated on a substrate containing corrosion-resistant SnO at a rotation speed of 5000 rpm and a speed of 2000 rpm / s. 2 On the substrate of the film, a double-layer SnO 2 The substrate is placed on a constant temperature heating table and annealed in air for 60 minutes at a temperature of 100° C. to obtain a substrate containing an electron transport layer;

[0089] (3) preparing a perovskite layer, comprising:

[0090] 1.4 mol FAI, 0.42 mol MACl and 1.53 mol PbI 2 Dissolved in 800 μL of DMF and 200 μL of DMSO to form a perovskite precursor solution; then, the prepared substrate containing the electron transport layer was cleaned with a plasma cleaner for 5 minutes, and after cleaning, it was transferred to a nitrogen glove box together with the solution, and the stirred perovskite precursor solution was spin-coated on the surface of the cleaned substrate containing the electron transport layer at a speed of 4500 rpm and a speed of 1500 rpm / s for 25 seconds, and 150 μL of chlorobenzene was added as an anti-solvent at the 17th second of spin coating. After spin coating, it was transferred to a constant temperature hot stage for annealing for 30 minutes, and the annealing temperature was 100°C to obtain a substrate containing a perovskite layer;

[0091] (4) Preparation of BAI passivation layer, including:

[0092] 2 mg BAI was dissolved in 1 ml isopropanol, and after being stirred evenly, the obtained solution was spin-coated on the substrate containing the perovskite layer at a rotation speed of 5000 rpm and a speed increase of 2000 rpm / s for 30 seconds, and then annealed in a nitrogen environment for 5 minutes at an annealing temperature of 80°C to obtain a substrate containing a BAI passivation layer;

[0093] (5) Preparation of a hole transport layer, comprising:

[0094] 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of tBP and 17.5 μL of Li-TFSI (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile) were added to obtain a Spiro-OMeTAD precursor solution. The precursor solution was spin-coated on a substrate containing a BAI passivation layer at a rotation speed of 4000 rpm and a rise speed of 1000 rpm / s for 30 s. After the spin coating was completed, the substrate was transferred to a drying cabinet and stored for 24 hours to obtain a substrate containing a hole transport layer;

[0095] (6) Preparation of metal electrodes, including:

[0096] A 100 nm silver layer was deposited as a metal electrode on a substrate containing a hole transport layer by thermal evaporation, wherein the deposition rate of 0 to 5 nm was The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate of 50-100 nm is Comparative perovskite solar cells were obtained.

[0097] Comparative Example 3

[0098] The comparative perovskite solar cell was prepared by the following steps:

[0099] (1) Pretreatment of the substrate: Cut the PEN / ITO substrate into 1.5×1.5 cm size, remove the surface protective film, and then use a UV ozone cleaning machine to clean for 30 min to obtain a pretreated substrate;

[0100] (2) preparing an electron transport layer, including:

[0101] Preparation of SnO by ALD 2Layer: After the sample chamber is inflated until the pressure reading reaches 760 torr, the chamber cover is opened and the pre-treated substrate is placed. The carrier gas flow rate is set to 30 sccm (1 sccm = 1 mL / min), the chamber temperature is 100 ° C, and after the temperature is stable for 120 s, ultrapure water pulse is sprayed for 0.015 s, and then wait for 4 s and then use TDMASn source pulse to spray for 0.1 s, wait for 4 s, and then cycle the process of ultrapure water pulse to TDMASn source pulse 250 times to complete the deposition. After the deposition is completed, wait for the temperature to drop back to 60 ° C to inflate and sample, and obtain 30nm corrosion-resistant SnO 2 The substrate of the film;

[0102] SnO 2 15% aqueous dispersion with H 2 O in a volume ratio of 1:5 and stirred evenly to obtain a dispersion, which was then spin-coated on a substrate containing corrosion-resistant SnO at a rotation speed of 5000 rpm and a speed of 2000 rpm / s. 2 On the substrate of the film, a double-layer SnO 2 The substrate is placed on a constant temperature heating table and annealed in air for 60 minutes at a temperature of 100° C. to obtain a substrate containing an electron transport layer;

[0103] (3) preparing a perovskite layer, comprising:

[0104] 1.4 mol FAI, 0.42 mol MACl and 1.53 mol PbI 2 Dissolved in 800 μL of DMF and 200 μL of DMSO to form a perovskite precursor solution; then, the prepared substrate containing the electron transport layer was cleaned with a plasma cleaner for 5 minutes, and after cleaning, it was transferred to a nitrogen glove box together with the solution, and the stirred perovskite precursor solution was spin-coated on the surface of the cleaned substrate containing the electron transport layer at a speed of 4500 rpm and a speed of 1500 rpm / s for 25 seconds, and 150 μL of chlorobenzene was added as an anti-solvent at the 17th second of spin coating. After spin coating, it was transferred to a constant temperature hot stage for annealing for 30 minutes, and the annealing temperature was 100°C to obtain a substrate containing a perovskite layer;

[0105] (4) Preparation of BAI passivation layer, including:

[0106] 2 mg BAI was dissolved in 1 ml isopropanol, and after being stirred evenly, the obtained solution was spin-coated on the substrate containing the perovskite layer at a rotation speed of 5000 rpm and a speed increase of 2000 rpm / s for 30 seconds, and then annealed in a nitrogen environment for 5 minutes at an annealing temperature of 80°C to obtain a substrate containing a BAI passivation layer;

[0107] (5) Preparation of a hole transport layer, comprising:

[0108] 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of tBP and 17.5 μL of Li-TFSI (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile) were added to obtain a Spiro-OMeTAD precursor solution. 35 μL of the precursor solution was transferred to a substrate containing a BAI passivation layer, and the substrate was spin-coated at a speed of 4000 rpm and a rise rate of 1000 rpm / s for 30 s. After the spin coating was completed, the substrate was transferred to a drying cabinet and stored for 24 hours to obtain a substrate containing a hole transport layer.

[0109] (6) Preparation of metal electrodes, including:

[0110] A 100 nm silver layer was deposited as a metal electrode on a substrate containing a hole transport layer by thermal evaporation, wherein the deposition rate of 0 to 5 nm was The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate of 50-100 nm is Comparative perovskite solar cells were obtained.

[0111] Comparative Example 4

[0112] The comparative perovskite solar cell was prepared by the following steps:

[0113] (1) Pretreatment of the substrate: Cut the PEN / ITO substrate into 1.5×1.5 cm size, remove the surface protective film, and then use a UV ozone cleaning machine to clean for 30 min to obtain a pretreated substrate;

[0114] (2) preparing an electron transport layer, including:

[0115] Preparation of SnO by ALD 2 Layer: After the sample chamber is inflated until the pressure reading reaches 760 torr, the chamber cover is opened and the pre-treated substrate is placed. The carrier gas flow rate is set to 30 sccm (1 sccm = 1 mL / min), the chamber temperature is 100 ° C, and after the temperature is stable for 120 s, ultrapure water pulse is sprayed for 0.015 s, and then wait for 4 s and then use TDMASn source pulse to spray for 0.1 s, wait for 4 s, and then cycle the process of ultrapure water pulse to TDMASn source pulse 417 times to complete the deposition. After the deposition is completed, wait for the temperature to drop back to 60 ° C to inflate and sample, and obtain 50nm corrosion-resistant SnO 2 The substrate of the film;

[0116] SnO 2 15% aqueous dispersion with H 2O in a volume ratio of 1:5 and stirred evenly to obtain a dispersion, which was then spin-coated on a substrate containing corrosion-resistant SnO at a rotation speed of 5000 rpm and a speed of 2000 rpm / s. 2 On the substrate of the film, a double-layer SnO 2 The substrate is placed on a constant temperature heating table and annealed in air for 60 minutes at a temperature of 100° C. to obtain a substrate containing an electron transport layer;

[0117] (3) preparing a perovskite layer, comprising:

[0118] 1.4 mol FAI, 0.42 mol MACl and 1.53 mol PbI 2 Dissolved in 800 μL of DMF and 200 μL of DMSO to form a perovskite precursor solution; then, the prepared substrate containing the electron transport layer was cleaned with a plasma cleaner for 5 minutes, and after cleaning, it was transferred to a nitrogen glove box together with the solution, and the stirred perovskite precursor solution was spin-coated on the surface of the cleaned substrate containing the electron transport layer at a speed of 4500 rpm and a speed of 1500 rpm / s for 25 seconds, and 150 μL of chlorobenzene was added as an anti-solvent at the 17th second of spin coating. After spin coating, it was transferred to a constant temperature hot stage for annealing for 30 minutes, and the annealing temperature was 100°C to obtain a substrate containing a perovskite layer;

[0119] (4) Preparation of BAI passivation layer, including:

[0120] 2 mg BAI was dissolved in 1 ml isopropanol, and after being stirred evenly, the obtained solution was spin-coated on the substrate containing the perovskite layer at a rotation speed of 5000 rpm and a speed increase of 2000 rpm / s for 30 seconds, and then annealed in a nitrogen environment for 5 minutes at an annealing temperature of 80°C to obtain a substrate containing a BAI passivation layer;

[0121] (5) Preparation of a hole transport layer, comprising:

[0122] 72.3 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene, and 28.8 μL of tBP and 17.5 μL of Li-TFSI (520 mg of Li-TFSI was dissolved in 1 mL of acetonitrile) were added to obtain a Spiro-OMeTAD precursor solution. 35 μL of the precursor solution was transferred to a substrate containing a BAI passivation layer, and the substrate was spin-coated at a speed of 4000 rpm and a rise rate of 1000 rpm / s for 30 s. After the spin coating was completed, the substrate was transferred to a drying cabinet and stored for 24 hours to obtain a substrate containing a hole transport layer.

[0123] (6) Preparation of metal electrodes, including:

[0124] A 100 nm silver layer was deposited as a metal electrode on a substrate containing a hole transport layer by thermal evaporation, wherein the deposition rate of 0 to 5 nm was The deposition rate of 5-10nm is The deposition rate of 10-20nm is The deposition rate of 20-50nm is The deposition rate of 50-100 nm is Comparative perovskite solar cells were obtained.

[0125] The above Example 1 and Comparative Examples 1-3 are used to obtain the corrosion-resistant SnO 2 The microstructure of the film substrate can be characterized as shown in the attached Figure 2 AFM contrast images and attached Figure 3 The SEM contrast images shown. Figure 2 It can be seen that the corrosion-resistant SnO 2 The surface roughness of the substrate of the film is 1.7nm, 3.4nm, 3.1nm and 1.8nm respectively. 2 After that, the roughness of the sample surface remained basically unchanged, indicating that SnO 2 It is grown on ITO (PEN) in a conformal manner, and then spin-coated with SnO 2 After the nanoparticles, the surface roughness decreased, indicating that the spin-coated SnO 2 Fill the surface depression. Figure 3 It can be seen that directly spin-coating SnO 2 The sample of (Comparative Example 1) has a large number of defects and cracks, and the ALD SnO 2 Then spin-coat SnO 2 The device has good crystallization, dense grains, good flatness, and uniform grain size. 2 The crystallization effect is best when the thickness is 30nm.

[0126] The ALD SnO2 substrate obtained in Example 1 and the SnO2 substrates of Comparative Examples 1-3 were measured by atomic force microscopy. 2 The substrate was spin-coated with a perovskite layer and the results are shown in the attached figure. Figure 4 As shown, it can be seen that after using ALD, more nanoscale pores appear in the film and the roughness of the film is lower (the roughness value is 33.846nm, which is significantly lower than 44.199nm of the control group).

[0127] Furthermore, the perovskite solar cells obtained in Example 1 and Comparative Examples 1 and 3 were characterized by X-ray diffraction, and the results are shown in the attached figure. Figure 5 As shown, it can be seen that in SnO 2The perovskite film prepared on the electron transport layer shows a simple FAPbI 3 Phase, there are two strongest diffraction peaks at 14.04° and 28.02°, corresponding to the structure of the (100) and (200) crystal planes of the perovskite crystal, and the broad diffraction peak at about 26.8° is a typical feature of the polymer PEN substrate. The results show that the perovskite film prepared in Example 1 has the strongest diffraction peak and the perovskite crystallization effect is the best.

[0128] Furthermore, the power conversion efficiency, current density (Jsc), opening voltage (Voc) and fill factor (FF) of the perovskite solar cells obtained in Example 1 and Comparative Examples 1-3 were compared and tested, and the results are shown in the attached figure. Figure 6 As shown, the test results of Example 1 are shown in the attached Figure 7 As shown. Figure 6 , 7 It can be seen that the photoelectric performance of the perovskite solar cell of the present invention is significantly better than that of conventional devices. 2 Under the irradiation of simulated sunlight, the open circuit photovoltage of the perovskite solar cell of Example 1 is 1.14 V and the short circuit photocurrent is 24.75 mA / cm 2 , the photoelectric conversion efficiency is 23.51%.

[0129] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a flexible perovskite solar cell, characterized in that: It includes: Obtaining a substrate for depositing an electron transport layer for a flexible perovskite solar cell; preparing a flexible perovskite solar cell electron transport layer on the substrate; Preparing a perovskite layer on the flexible perovskite solar cell electron transport layer; preparing an n-butylammonium iodide passivation layer on the perovskite layer; preparing a hole transport layer on the n-butylammonium iodide passivation layer; preparing a metal electrode on the hole transport layer; Wherein, the preparation of the flexible perovskite solar cell electron transport layer comprises: (1) depositing a SnO2 layer on a substrate by an atomic layer deposition method to obtain a SnO2 deposition layer; (2) spin coating a SnO2 dispersion doped with glycine hydrochloride onto the SnO2 deposited layer to form a SnO2 spin-coated layer, and subjecting the obtained double SnO2 layer structure containing the SnO2 deposited layer and the SnO2 spin-coated layer to a first annealing treatment in air at a temperature of 80-100° C. to obtain the flexible perovskite solar electron transport layer. Wherein, the obtaining of the SnO2 dispersion doped with glycine hydrochloride comprises: The SnO2 aqueous dispersion is added to the deionized water solution of glycine hydrochloride and mixed evenly to obtain the SnO2 dispersion doped with glycine hydrochloride.

2. The preparation method according to claim 1, characterized in that: in, The thickness of the SnO2 deposited layer is 18-50 nm; and / or the thickness of the SnO2 spin-coated layer is 20-30 nm.

3. The preparation method according to claim 2, characterized in that: The thickness of the SnO2 deposited layer is 30 nm; and / or the thickness of the SnO2 spin-coated layer is 25-35 nm.

4. The preparation method according to claim 1, characterized in that: The concentration of SnO2 in the SnO2 aqueous dispersion is 10-20wt%; the volume ratio of the deionized water solution of glycine hydrochloride to the SnO2 aqueous dispersion is 4-6:

1.

5. The preparation method according to claim 1, characterized in that: in, The atomic layer deposition method comprises: -4 Pa-4×10 -4 Pa, a carrier gas flow rate of 20-40sccm, and a temperature of 80-100°C, the following are performed: (a) ultrapure water pulse spraying for 0.01-0.02s, and waiting for 3-5s; (b) tetrakis(dimethylamino)tin source pulse spraying for 0.05-0.15s, and waiting for 3-5s; then repeating the process of (a)-(b) 200-300 times, and then naturally cooling to 55-65°C; and / or, the spin coating includes: spin coating the SnO2 dispersion doped with glycine hydrochloride on the SnO2 deposition layer at a rotation speed of 4000-5000rpm and a ramp rate of 1000-2500rpm / s.

6. The preparation method according to claim 1, characterized in that: The substrate is selected from polyethylene terephthalate coated with indium tin oxide conductive material.

7. The preparation method according to claim 1, characterized in that: It includes: (1) pretreating a polyethylene terephthalate-coated indium tin oxide conductive material substrate by ultraviolet light to obtain a pretreated substrate; (2) preparing the flexible perovskite solar cell electron transport layer on the pretreated substrate to obtain a substrate containing the electron transport layer; (3) dissolving formamidine hydroiodide, methylammonium chloride, and lead iodide in a mixed solution of N,N-dimethylformamide and dimethyl sulfoxide to form a perovskite precursor solution, and spin-coating the solution on the substrate containing the electron transport layer, adding chlorobenzene dropwise during the spin-coating process, and performing a second annealing treatment after the spin-coating is completed to obtain a substrate containing the perovskite layer; (4) dissolving the passivating agent n-butylammonium iodide in isopropanol to obtain a passivating precursor solution, and spin-coating the solution on the substrate of the perovskite layer. After the spin coating is completed, a third annealing treatment is performed to obtain a substrate containing a passivation layer; (5) dissolving 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene, adding 4-tert-butylpyridine and an acetonitrile solution of lithium bis(trifluoromethane)sulfonyl imide to obtain a hole precursor solution, spin-coating the solution on the substrate containing the passivation layer, and drying the solution after spin coating to obtain a substrate containing a hole transport layer; (6) depositing silver as a metal electrode on the substrate containing the hole transport layer by thermal evaporation to obtain a flexible perovskite solar cell; Wherein, the temperature of the second annealing treatment is 80-100° C., and the time is 10-40 min; and / or, the temperature of the third annealing treatment is 70-90° C., and the time is 1-10 min.

8. The preparation method according to claim 7, characterized in that: In the perovskite precursor solution, the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is 1:4, the concentration of methylamine chloride is 0.1-1.0 mol / ml, the concentration of formamidine hydroiodide is 1.0-2.0 mol / ml, and the concentration of lead iodide is 1.0-2.0 mol / ml; and / or, in the passivation precursor solution, the concentration of n-butylammonium iodide is 0.5-5 mg / mL.

9. The preparation method according to claim 7, characterized in that: The deposition rate of the deposited silver is Its thickness is 50-200nm.

10. A flexible perovskite solar cell prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Modification method for SnO2 electron selective transmission layer

    CN110504362A

  • Tin oxide electronic paste and preparation method and application thereof

    CN114023887A

  • Preparation method of lead-tin alloy perovskite solar cell based on glycine hydrochloride modification

    CN115942844A

  • Doped tin dioxide electron transport layer, flexible perovskite solar cell and preparation method of flexible perovskite solar cell

    CN118302006A

  • Preparation method of perovskite solar cell

    CN118613117A